Growth, nutritional quality, and energy use efficiency in two lettuce cultivars as influenced by white plus red versus red plus blue LEDs - Yan, Zhengnan; He, Dongxian; Niu, Genhua; Zhou, Qing; Qu, Yinghua (International Journal of Agricultural and Biological Engineering, 2020)
Red plus blue light-emitting diodes (LEDs) are commonly applied in plant factories with artificial lighting due to photosynthetic pigments, which absorb strongly in red and blue light regions of the spectrum. However, plants grown under natural environment are used to utilizing broad-wide spectrum by long-term evolution. In order to examine the effects of addition light added in red plus blue LEDs or white LEDs, green and purple leaf lettuces (Lactuca sativa L. cv. Lvdie and Ziya) were hydroponically cultivated for 20 days under white LEDs, white plus red LEDs, red plus blue LEDs, and red plus blue LEDs supplemented with ultraviolet, green or far-red light, respectively. The results indicated that the addition of far-red light in red plus blue LEDs increased leaf fresh and dry weights of green leaf lettuce by 28% and 34%, respectively. Addition of ultraviolet light did not induce any differences in growth and energy use efficiency in both lettuce cultivars, while supplementing green light with red plus blue LEDs reduced the vitamin C content of green leaf lettuce by 44% and anthocyanin content of purple leaf lettuce by 30% compared with red plus blue LEDs, respectively. Spectral absorbencies of purple leaf lettuce grown under red plus blue LEDs supplemented with green light were lower in green light region compared with those grown under red plus blue LEDs, which was associated with anthocyanin contents. White plus red LEDs significantly increased leaf fresh and dry weights of purple leaf lettuce by 25%, and no significant differences were observed in vitamin C and nitrate contents compared with white LEDs. Fresh weight, light and electrical energy use efficiencies of hydroponic green and purple leaf lettuces grown under white plus red LEDs were higher or no significant differences compared with those grown under red plus blue LEDs. In conclusion, white plus red LEDs were suggested to substitute for red plus blue LEDs in hydroponic lettuce (cv. Lvdie and Ziya) production in plant factories with artificial lighting.Keywords: plant factory, hydroponic lettuce, light-emitting diodes (LED), light energy use efficiency, artificial lighting, absorption spectrum, anthocyanin content, photosynthetic pigmentsDOI: 10.25165/j.ijabe.20201302.5135Citation: Yan Z N, He D X, Niu G H, Zhou Q, Qu Y H. Growth, nutritional quality, and energy use efficiency in two lettuce cultivars as influenced by white plus red versus red plus blue LEDs. Int J Agric & Biol Eng, 2020; 13(2): 33–40.